Dry Eye Syndrome Modern Diagnostic Techniques and Advanced Treatments - Ferreri, Felicia M. (IntechOpen, 2022)
Dry eye syndrome is one of the most common types of ocular surface disorders that significantly worsen the quality of life of tens of millions of people worldwide.In the last decades, researchers worldwide investigated the composition and regulatory mechanisms of the preocular tear film to better understand dry eye syndrome. The tear film, in fact, plays a critical role in maintaining corneal and conjunctival integrity, protecting the eyes against infections, and preserving visual acuity. Recent scientific discoveries helped us gain a more and more accurate understanding of the structure and functioning of the tear film and how disorders in the tear film relate to dry eye syndrome. Today, ophthalmologists benefit from sophisticated diagnostic techniques, and they have at their disposal a wide range of effective therapeutic options to manage dry eye syndrome. This book illustrates the most recent research results in the diagnosis and treatment of dry eye syndrome, and it is of interest to the broad audience that comprises ophthalmologists, researchers, and students.